2020
DOI: 10.1186/s12944-020-01245-3
|View full text |Cite|
|
Sign up to set email alerts
|

The intake assessment of diverse dietary patterns on childhood hypertension: alleviating the blood pressure and lipidemic factors with low-sodium seafood rich in omega-3 fatty acids

Abstract: Background: Childhood hypertension (CH) is related to the dietary intake and diversity of children. The study aimed to assess the critical role of dietary diversity, and seafood long-chain n-3 polyunsaturated fatty acids (LC n-3 PUFAs) in reducing CH among the Iranian community. Methods: A cross-sectional two-phase study with 7-12-year-old Iranian students was designed. In the initial phase, the socio-demographic characteristics, and blood pressure status (normal, pre-hypertension, and hypertension) based on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Recent data analysis of 354 participants with reduced birth weight aged 8–15 years showed that, as compared with children with the lowest tertile of intake, those who had the highest tertile of dietary EPA and DHA intake had significantly lower SBP (−4.9 mmHg, 95% CI: −9.7 to −0.1) and pulse pressure (−7.7 mmHg, 95% CI: −15.0 to −0.4) ( 53 ). A cross-sectional study found that the childhood prehypertension and hypertension prevalence rates were 7.8 and 9.15%, and a regular seafood-rich dietary pattern with high ω-3 PUFAs contents was significantly associated with a reduction in BP in hypertensive children and a decrease in the risk of CH in normotensive children ( 54 ). A recent study indicated that maternal DHA intake with 600 mg during pregnancy appeared to mitigate the association between childhood overweight condition/obesity and BP (SBP:104.28 vs. 100.34 mmHg; DBP:64.7 vs. 59.76 mmHg) ( 55 ).…”
Section: ω-3 Pufas and Cardiovascular Disordersmentioning
confidence: 99%
“…Recent data analysis of 354 participants with reduced birth weight aged 8–15 years showed that, as compared with children with the lowest tertile of intake, those who had the highest tertile of dietary EPA and DHA intake had significantly lower SBP (−4.9 mmHg, 95% CI: −9.7 to −0.1) and pulse pressure (−7.7 mmHg, 95% CI: −15.0 to −0.4) ( 53 ). A cross-sectional study found that the childhood prehypertension and hypertension prevalence rates were 7.8 and 9.15%, and a regular seafood-rich dietary pattern with high ω-3 PUFAs contents was significantly associated with a reduction in BP in hypertensive children and a decrease in the risk of CH in normotensive children ( 54 ). A recent study indicated that maternal DHA intake with 600 mg during pregnancy appeared to mitigate the association between childhood overweight condition/obesity and BP (SBP:104.28 vs. 100.34 mmHg; DBP:64.7 vs. 59.76 mmHg) ( 55 ).…”
Section: ω-3 Pufas and Cardiovascular Disordersmentioning
confidence: 99%
“…14 It is therefore possible that the positive correlation of the EPA/AA ratio with TG, BMI, and the degree of obesity may be childhood specific. Given also that TG and omega-3 polyunsaturated fatty acid levels are decreased, even in children given sea foods, 15 it is likely that the fish intake may have affected their TG and EPA levels. It is also likely that children who overeat may have consumed a great deal more fish than other children thus contributing to the positive correlation between EPA/AA ratios and BMI, degree of obesity, and HOMA-IR in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This pathogen often causes severe inflammation and short-term (e.g., fever, dysuria, and flank pain) and long-term (e.g., irreversible renal scarring) morbidities [ 7 , 8 ]. The renal scarring significantly develops the risk of hypertension, proteinuria, vesicoureteral reflux (VUR), chronic kidney disease, and end-stage renal disease [ 9 , 10 ]. Since renal scarring is observed in 37% of AP children after two years from the infection onset, the rapid diagnosis and implementation of effective therapeutic measures are necessary to manage this disease among children [ 4 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%